Intestinal mucosa development in broiler chickens fed natural growth promoters - Pelicano, ERL [UNESP]; Souza, PA [UNESP]; Souza, HBA [UNESP]; Figueiredo, DF [UNESP]; Boiago, MM [UNESP]; Carvalho, SR [UNESP]; Bordon, VF [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
This study evaluated the use of probiotics and prebiotics on the histological and morphological indexes of the intestinal mucosa of broilers at 21 days of age. Thirty-six birds were randomly distributed in a 3 x 3 factorial arrangement, considering 3 probiotics and prebiotics sources in the diet. There were 9 treatments with 4 repetitions. Diet treatments were: 1 - Control (without growth promoters); 2 - Bacillus subtilis-based probiotic (Pro 1); 3 - Probiotic (Pool) based on Lactobacillus acidophilus and casei, Streptococcus lactis and faecium, Bifidobacterium bifidum and Aspergillus oryzae (Pro 2); 4 - Prebiotic based on Phosphorylated Mannanoligosaccharide (MOS) and Organic Acidifier (OA) (Pre 1); 5 - MOS-based prebiotic (Pre 2); 6 - Pro 1 + Pre 1; 7 - Pro 1 + Pre 2; 8 - Pro 2 + Pre 1; 9 - Pro 2 + Pre 2. Higher villus height (VH) (p<0.01) were seen in the duodenum of birds fed diets without prebiotics, whereas birds fed Bacillus subtilis-based probiotic and birds fed prebiotic based on MOS and OA showed higher VH (p<0.01) in jejunum and ileum. Greater crypt depths (CD) (p<0.01) were observed in the duodenum, jejunum and ileum of birds receiving B. subtilis, and in the duodenum and jejunum of birds fed diets without prebiotics. Significant interaction (p<0.01) between the evaluated factors was seen for both, VH and CD, in the three intestinal portions. Greater VH was obtained in duodenum, jejunum and ileum with the use of probiotics and prebiotics and greater CD with the use of probiotics, in relation to the control group. There was no difference in villus density (VD) between birds fed diets without additives or diets containing probiotics and prebiotics. Nevertheless, there was a significant interaction (p<0.05) between the evaluated factors for VD in the duodenum. Concluding, beneficial effects were seen in histological indexes of the intestinal mucosa with the use of probiotics and prebiotics at 21 days of age.
Keywords: Broilers; crypt depth; growth promoters; Intestinal morphology; villus density; villus height